2012
DOI: 10.1002/jso.23187
|View full text |Cite
|
Sign up to set email alerts
|

MAGIC in practice: Experience of peri‐operative ECF/X chemotherapy in gastro‐esophageal adenocarcinomas

Abstract: Our patient population is older than the patients in the MAGIC trial (age 66 years vs. 62 years) with a much higher proportion of esophageal and GEJ tumours. Overall, curative resection rate was comparable to the MAGIC trial. Overall survival is superior to that found in the MAGIC trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…In both studies toxicity associated with chemotherapy was high, and less than 50% of the patients were able to complete the scheduled treatment cycles. This is in accordance with two recent studies 15, 16 reporting the experience with the ECX/EOX regimen in a clinical setting. This raises questions as to the potential effect of preoperative (neoadjuvant) chemotherapy regimens alone, as severe toxicity and non‐compliance primarily was associated with the post‐surgery chemotherapy part.…”
Section: Discussionsupporting
confidence: 93%
“…In both studies toxicity associated with chemotherapy was high, and less than 50% of the patients were able to complete the scheduled treatment cycles. This is in accordance with two recent studies 15, 16 reporting the experience with the ECX/EOX regimen in a clinical setting. This raises questions as to the potential effect of preoperative (neoadjuvant) chemotherapy regimens alone, as severe toxicity and non‐compliance primarily was associated with the post‐surgery chemotherapy part.…”
Section: Discussionsupporting
confidence: 93%
“…The mid‐point Mandard TRG of 3 is defined as “fibrosis predominates” with chemotherapy appearing to provide some benefit, and so while TRG 3 may not have such a robust degree of response as TRG 1‐2, it cannot be grouped with TRG 4‐5 patients, who do not appear to have any tangible response to chemotherapy. Therefore, although Mandard 3 tumors do not display a significant degree of response, they have been loosely grouped with TRG 1‐2 tumors representing chemo‐sensitivity, as elsewhere in the literature …”
Section: Discussionmentioning
confidence: 99%
“…Patients administered ECX chemotherapy and undergoing surgery were included in the study on an intention to treat basis, however not all patients received the designated six cycles at full dose. Toxicity related complications are well documented with the ECX regimen so treatment regimens were modified if necessary to meet individual patient requirements. Therefore, a number of patients in our study group underwent dose reductions, cycle delays, and occasionally reduced cycle numbers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4 Conversely, an examination of 100 patients treated with MAGIC chemotherapy in Nottingham revealed that as many as 19% of those commencing MAGIC treatment with curative intent failed to proceed to surgery. 15 Although not demonstrated in the original trials, the longer and more aggressive chemotherapy given in a MAGIC regimen would intuitively be expected to result in greater toxicity and disease progression prior to surgery in resistant cases. As such, an intention-to-treat analysis (that included the survival outcomes of those who started treatment but did not undergo surgery) would be a more accurate comparison.…”
Section: Discussionmentioning
confidence: 99%